Technological Adaptation, Trade, and Growth - Chong, Alberto; Zanforlin, Luisa (Washington, D.C. : International Monetary Fund, 2000)
This paper extends Grossman and Helpman's seminal work (1991), and presents an endogenous growth model where innovations created in a high-tech sector may be assimilated or adapted by a low-tech sector. Applying a simple Heckscher-Ohlin framework, the effects of technological diffusion are found to allow a country relatively scarce in human capital to benefit from nondecreasing rates of growth through its low-tech sector. The model is tested by using a dynamic panel data approach (Arellano and Bover, 1995). Results are consistent with the predictions of the model and robust to a broad range of definitions of technological intensity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet